NUDT15 R139C Variants Increase the Risk of Azathioprine-Induced Leukopenia in Chinese Autoimmune Patients - Fei, Xiang; Shu, Qing; Zhu, Huaijun; Hua, Bingzhu; Wang, Shiying; Guo, Ling; Fang, Yun; Ge, Weihong (Frontiers in Pharmacology, 2018)
The aim of this study was to investigate the influence of NUDT15 R139C, thiopurine S-methyltransferase (TPMT) and 6-TGN on azathioprine (AZA) induced leukopenia in Chinese autoimmune patients. Among 87 enrolled patients, 23 (26.4%) had leukopenia. The NUDT15 R139C variant was associated with leukopenia (p = 1.86×10-7 ; OR: 7.59; 95% CI: 3.16-18.21). However, TPMT genotype was not shown to be correlated with the incidence of leukopenia (p = 0.95). There was no significant difference of 6-TGN concentration between patients with or without leukopenia (p = 0.15) and no association was found in patients with NUDT15 R139C variants alleles (p = 0.62). Finally, we found that the range of 6-TGN concentrations in autoimmune diseases was much lower than the established 6-TGN monitoring range for inflammatory bowel diseases. Therefore, the variant of NUDT15 R139C is strongly associated with AZA-induced leukopenia in Chinese patients with various autoimmune diseases such as systemic lupus erythematosus, Sjögren's syndrome, etc.